Pengaruh Pengetahuan Tentang Sampah dan Ketersediaan Sarana Prasarana Terhadap Perilaku Ibu Membuang Sampah yang Berpotensi Bencana Banjir di Daerah Aliran Sungai Deli Kota Medan - Alvionita, Rini; Susilawati, Susilawati (Innovative: Journal Of Social Science Research, 2025)
The results of the initial survey revealed that the general public is not well-versed in the process of creating sampah and that there is a lack of sarana and prasarana for doing so. This could be the result of reckless parents dumping sampah in the Deli River, causing flooding in Medan. The purpose of this exploratory study is to determine how parents' perceptions of the utility, efficacy, safety, and availability of sanitation facilities can lead to flooding in the Deli Kota Medan area. This study identified 14.956 aging parents living in the Sungai Deli neighbourhood of Medan. Rumus Slovin was used to select 99 research samples. This study used a 95% confidence interval regression to analyze data. The findings indicate that public awareness of the benefits, drawbacks, and limitations of tindakan pengelolaan sampah, as well as the availability of sarana prasarana, has an impact on ibu-ibu behaviour when collecting sampah in the Sungai Deli area, which can lead to banjir. It is suggested that the Dinas Kebersihan, Kebersihan Kota Medan, and related organizations use sampah pengangkut. The government of Medan must establish regulations about the amount of money required to improve the dialling of Sungai Deli, create a work schedule every two years, and engage LSM, puskesmas, desa siaga/promotor lingkungan hidup, and other communities in the process of banjir development.